Knowledge levels of family medicine residents regarding smoking cessation counseling: the effect of an educational program - Topuz, Ayşe Nur; Özer, Zeliha Yelda; Çetinkaya, Pelin Duru; Kurdak, Hatice; Ergün, Bahadır; Turan, Ayşe; Özcan, Sevgi (Journal of Dependence, 2026)
Objective: Screening for tobacco use and providing brief smoking cessation interventions are among the most cost-effective preventive services in primary care. Family physicians play a key role in tobacco control; however, in Türkiye, family medicine residents have limited access to Ministry of Health smoking cessation training programs. To address this gap, a brief training was incorporated into the residency curriculum. This study evaluated its effect on residents’ knowledge regarding smoking cessation counseling. Methods: This single-group pretest–posttest study included 66 family medicine residents at the Department of Family Medicine, Çukurova University Faculty of Medicine. Participants received a three-hour theoretical training delivered by a pulmonologist involved in Ministry of Health smoking cessation programs. Knowledge was assessed using a questionnaire administered before and after the training. Analyses were conducted with residents who completed both assessments. Results: The mean age was 31.68 ± 7.31 years, and 56.1% were female. Current smokers comprised 18.2%, and 4.5% were former smokers. Only 10.6% had prior experience in a smoking cessation clinic. Most residents (69.7%) perceived their knowledge as partially sufficient, and 7.6% considered it adequate; 95.5% expressed willingness to receive training. Post-training knowledge scores increased significantly compared with pre-training scores (10.70 ± 3.19 vs. 13.87 ± 2.71; t(60) = –6.203; p < 0.001). Conclusion: A brief three-hour theoretical training significantly improved residents’ knowledge of smoking cessation counseling. Integrating clinic rotations and evaluating long-term outcomes may further strengthen effectiveness.